Polemik CALISTUNG untuk Anak Usia Dini (Telaah Konsep Development Approriate Practice) - Nasir, Amin (THUFULA, 2018)
The problem of reading, writing and numeracy (calistung) for early childhood is a very dilemmatic phenomenon. At this time, many elementary school (SD) have a high standard of competence. Prospectif elementary students must take the test read,write,and numeracy to enter elementary school. Whereas learning in Kindergarden (TK) calistung only introduction. Kindergarden education program is more emphasized on the activity of playing as well a character building. The fact is, many kindergarden even play groups, especially in big cities have taught calistung and have a target to know calistung after they come out. This raises a polemic regarding calistung for early childhood.